Contribution of Historical Global Warming to Local‐Scale Heavy Precipitation in Western Japan Estimated by Large Ensemble High‐Resolution Simulations. Issue 12 (19th June 2019) - Kawase, H.; Imada, Y.; Sasaki, H.; Nakaegawa, T.; Murata, A.; Nosaka, M.; Takayabu, I.
Abstract: Large ensemble pairs of high‐resolution global and regional climate simulations, which are composed of 100 members of 60 years each, make it possible to attribute changes in local‐scale heavy precipitation to historical global warming. Mountain ranges separate local climates and can modulate the impact of global warming on heavy precipitation. In the summer, Japan's Kyushu region, with mountain ranges approximately 200‐km long from south to north, receives large amounts of precipitation. Over western Kyushu, the monthly maximum daily precipitation ( maxPr daily ) in July increases due to historical global warming, while the maxPrdaily is unchanged over eastern Kyushu. Moisture advection and convergence due to stationary weather fronts are primary factors causing heavy precipitation in western Kyushu and moistening due to warming increases the maxPrdaily . On the other hand, typhoons heading to Kyushu are related to heavy precipitation over eastern Kyushu. The changes in typhoons heading to Kyushu result in unchanged maxPrdaily in eastern Kyushu. Our results suggest that local‐scale mountain ranges can change synoptic‐scale disturbances causing heavy precipitation and modulate the impact of historical global warming on heavy precipitation across mountain ranges. Plain Language Summary: Global warming has already increased heavy precipitation, but the impact of global warming on heavy precipitation depends on the region. Mountain ranges separate local climates. Different synoptic disturbances cause heavy precipitation over one side of the mountain ranges. For instance, the advection and convergence of water vapor due to a stationary weather front cause heavy precipitation on the western sides of mountain ranges in the third‐largest island in Japan, while typhoons cause heavy precipitation in the eastern side of mountain ranges. Since the impacts of global warming on these synoptic phenomena are different, the changes in heavy precipitation over each side of the mountain ranges are also different. Key Points: Large ensemble simulations indicate that historical global warming has already changed the frequency of heavy precipitation in Japan Local‐scale heavy precipitation is caused by different synoptic conditions over the western and eastern sides of mountain ranges The contribution of global warming to the frequency of heavy precipitation depends on synoptic disturbances causing heavy precipitation